Electrocardiographic effect of artemisinin-piperaquine, dihydroartemisinin-piperaquine, and artemether-lumefantrine treatment in falciparum malaria patients - Wu,Wanting (2021)
Abstract INTRODUCTION: Artemisinin-based combination therapy (ACT), such as artemisinin-piperaquine (AP), dihydroartemisinin-piperaquine (DP), and artemether-lumefantrine (AL), is the first-line treatment for malaria in many malaria-endemic areas. However, we lack a detailed evaluation of the cardiotoxicity of these ACTs. This study aimed to analyze the electrocardiographic effects of these three ACTs in malaria patients. METHODS: We analyzed the clinical data of 89 hospitalized patients with falciparum malaria who had received oral doses of three different ACTs. According to the ACTs administered, these patients were divided into three treatment groups: 27 treated with AP (Artequick), 31 with DP (Artekin), and 31 with AL (Coartem). Electrocardiograms and other indicators were recorded before and after the treatment. The QT interval was calculated using Fridericia’s formula (QTcF) and Bazett’s formula (QTcB). RESULTS: Both QTcF and QTcB interval prolongation occurred in all three groups. The incidence of such prolongation between the three groups was not significantly different. The incidence of both moderate and severe prolongation was not significantly different between the three groups. The ΔQTcF and ΔQTcB of the three groups were not significantly different. The intra-group comparison showed significant prolongation of QTcF after AL treatment. CONCLUSIONS: Clinically recommended doses of DP, AL, and AP may cause QT prolongation in some malaria patients but do not cause torsades de pointes ventricular tachycardia or other arrhythmias.